Awareness and Treatment Decisions on Tooth Wear among Jordanian Dentists and Prosthodontists: A Cross-Sectional Survey Study - Samiha Sartawi; Nesreen A. Salim; Duaa Taim (International Journal of Dentistry)
Objectives. To assess the awareness, knowledge, and treatment decisions by dentists in Jordan regarding tooth wear. Materials and Methods. A questionnaire was disseminated to a random sample of 200 general dentists and 100 prosthodontists working in the Ministry of Health, academia, private practices, and military services. Chi square and independent t-tests were performed for statistical analysis. Results. Hundred and seventy-nine dentists and prosthodontists responded (59.7% response rate), of which 71.5% was females. 83.8% of the dentists reported they see patients with tooth wear. 61.5% registered wear lesions in the patient file, and 68.2% reported they find a probable cause of tooth wear. 87.2% of the dentists reported that bruxism is the most common cause in Jordan. 63.3% dentists treated their patients. 46.4% reported they “always” record a dietary history. 77.7% did not think that tooth wear is linked to caries. Low confidence levels were demonstrated among general practitioners in diagnosing and treating tooth wear. Regarding treatment decisions, most dentists decided to restore worn teeth with composite and to construct a night guard. Minimally affected anterior teeth were mostly treated with fluoride. Restoration of posterior worn teeth with overlay was suggested by one-third of the dentists. Conclusion. The dentists and prosthodontists in Jordan are aware of tooth wear. However, examination and documentation were given a little priority by general dentists. On the other hand, there was an agreement among the dentists and prosthodontists on applying the minimally invasive approach. Clinical Significance. It is challenging for dentists to make the best treatment decision for tooth wear especially as no standard treatment is available. Therefore, this study investigated the awareness and treatment decisions of a sample of dentists and prosthodontists in Jordan.